Event Timestamping Tool: a simple PC based kernel to timestamp distributed events - Martins, Pedro (2000)
This report describes the design and implementation of a tool to timestamp distributed events, using a standard PC hardware platform. The Event Timestamping Tool (ETT) is a small software kernel that detects externally generated events using two probe sources, and stores the respective timestamps with known precision bounds. A specialized kernel solution minimizes the response time for an event detection and registration and, consequently, maximizes the precision of the tool. Our approach exploits the Pentium processor internal timestamp counter to provide timestamps with fine granularity